2013
DOI: 10.1902/jop.2012.110656
|View full text |Cite
|
Sign up to set email alerts
|

Enamel Matrix Derivative, Alone or Associated With a Synthetic Bone Substitute, in the Treatment of 1‐ to 2‐Wall Periodontal Defects

Abstract: Our data support the hypothesis that the adjunct of an HA/β-TCP composite implant with EMD may improve the clinical and radiographic outcomes of the surgical treatment of unfavorable intrabony defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
47
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 46 publications
(129 reference statements)
7
47
3
Order By: Relevance
“…The summary of quality assessment was described in Descriptive data relative to the included twelve studies are reported in months in one study [14].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…The summary of quality assessment was described in Descriptive data relative to the included twelve studies are reported in months in one study [14].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Only one paper did not report smoking habits [20]. Five drop-outs were reported in three studies [14,34,36]. Patients enrolled in four studies suffered from chronic periodontitis [18, 28, 32, 36], whereas in one study patients suffering from chronic and aggressive periodontitis…”
Section: Patient's Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 19 studies included, nine had a split-mouth design -six with a follow-up period of 12 months (14,16,23,27,28,34) and three with duration of over 24 months (15,35,36) -and ten had a parallel design -five with a follow-up period of 12 months (10,17,(37)(38)(39) and five with a follow-up period of over 24 months (24,25,29,40,41). Regarding the evaluated outcomes, PD and CAL were evaluated in all the studies, gingival recession (GR) was additionally evaluated in eight studies (15,16,24,25,29,36,39,41) and bone filling in twelve studies (10,(14)(15)(16)(23)(24)(25)27,29,36,39,41).…”
Section: Study Characteristicsmentioning
confidence: 99%